Quality restoration of waste polyolefin plastic material through the dissolution-reprecipitation technique - Arkan Jasim, Hadi; Najmuldeen, Ghazi Faisal; Ahmed, Iqbal (CI and CEQ, 2014)
This study examines the restoration of waste plastic polymers based on LDPE, HDPE or PP through dissolution/reprecipitation. Experimental conditions of the recycling process, including type of solvent/non-solvent, original polymer concentration and dissolution temperature were optimized. Results revealed that by using the different prepared solvents/non-solvents at various ratios and temperatures, the polymer recovery was always greater than 94%. The FTIR spectra and the thermal properties (melting point and crystallinity) of the polymers before and after recycling were measured using Differential Scanning Calorimetry (DSC). Mechanical properties of the waste polymer before and after recycling were also measured. Besides small occasional deviations, the properties did not change. The tensile strength at maximum load was 7.1, 18.8, and 7.4 MPa for the recycled LDPE, HDPE and PP, respectively and 7.78, 18.54 and 7.86 MPa for the virgin polymer. For the waste, the strength was 6.2, 15.58 and 6.76 MPa.